Valuasi Ekonomi Kerusakan Lingkungan Akibat Kebakaran Gambut Di Desa Mak Teduh Provinsi Riau - Bambang Hero Saharjo; Basuki Wasis (Jurnal Silvikultur Tropika, 2019)
Peat fires caused negative impact which link to the death of flora, soil damage and smoke disasters.The research proposed to know how big the danger at environment due to forest fire. Unfortunately has so way research found how much money last during burning which link to end damage. Field observation and soil samples were taken through purposive sampling. The result of research show that fire cause a total death of flora and fauna and subsidence of 10-20 cm. This study showed that land fires significantly affected organic C, bulk density, and total microorganisms, and significanlyt effecedt on pH and respiration parameters. Our results clearly demonstrate the severe enviromental destruction due to on peat fire as it fulfill. The order to know the significance of the vegetation impact of fire that we use PP 4/2004. The order to know the significant of the negative impact of fire the we use PP 4/2004 for soil pH, organic C, bulk density, porosity, water content, total microorganisms, and respiration with the economic valuation ofer, damage due to fire was reached Rp1.765.190.064,-.Keywords : enviromental damage, economic valution. peat fires, soil properties